SAC Application as an Android-Based Arabic Interactive Media: Validator and User Perspectives - Paputungan , Moh. Zulkifli; N. Hula, Ibnu Rawandhy; Mariana, Ana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to decipher the results of validation tests and find out the user's response to the development of Android-based learning media using the Smart Apps Creator (SAC) application. This study uses mixed methods (quantitative and qualitative). Data collection uses questionnaires and documents. Quantitative analysis techniques were carried out on validation results using numbers, scales, or percentages, while qualitative analysis was carried out on the results of (1) individual trials, (2) small groups and (3) large groups. The population of this study is 30 grade VII students, while the sample is determined using non-probability sampling which aims to make all populations as samples. The results of the study show that: (1) the results of the validation of media experts obtained a percentage of 95% (very feasible) and material experts 94% (very feasible). (2) the results of user trials on the development of Android-based Arabic learning media products received an average score for individual trials of 80% with categories (good), small group trials of 85% with categories (very good) and large group trials of 95% with categories (very good).